Corpus linguistics for grammar : a guide for research - Jones, Christian, (Linguist); Waller, Daniel, (Linguist) (London : Routledge, 2015)
'Corpus Linguistics for Grammar provides an accessible and practical overview of how we can use corpus linguistics to analyse grammar. It examines the kinds of corpora available and the tools which can be used to analyse them, demonstrates how features of grammar can be explored using corpora, and provides three illustrative examples of research projects based on corpus data. Targeted at final year undergraduate and postgraduate university students studying within the areas of English Language, Literature, Applied Linguistics and TESOL, this book will be essential reading for any students undertaking grammar corpus research'--
Includes bibliographical references and index.
Keywords: English language -- Grammar -- Study and teaching (Higher) -- Foreign speakers; English language -- Study and teaching (Higher) -- Foreign speakers; English language -- Grammar -- Research; Second language acquisition -- study and teaching -- Foreign speakers; Vocabulary -- Study and teaching (Higher).; Corpora (Linguistics).